Thin ferrihydrite sediment capping sequestrates phosphorus experiencing redox conditions in a shallow temperate lacustrine wetland. (October 2017) - Zou, Yuanchun; Grace, Michael R.; Roberts, Keryn L.; Yu, Xiaofei
Abstract: Synthesized ferrihydrite (Fh) with the dosages of 0.3, 0.6 and 0.9 cm thickness (labeled as Fh, 2Fh and 3Fh respectively, equivalent to 248–774 g/m 2 ) were deployed to serve as the reactive capping layer covering the Ornamental Lake sediments, the Royal Botanic Garden of Melbourne. The sediments were exposed to an alternating regime of oxic/anoxic conditions using laboratory reactors for 45 days. Dynamics of dissolved oxygen (DO), pH, filterable reactive phosphorus (FRP), filterable ammonium (NH4 + ), nitrate and nitrite (NOx ), total dissolved nitrogen (TDN) and dissolved iron (Fe) of overlying water were examined. After incubation, O2 and H2 S profiles across the water-sediment interface were observed with microelectrodes. The element distributions in the upper sediments were tested as well. Results showed that DO and pH kept relatively stable during oxic period, while decreased significantly during anoxic period. Fh cappings decreased both DO and pH, and inhibited the release of FRP. No significant increments of FRP in overlying waters were observedduring anoxic period. Fh cappings prompted the releases of NH4 + and TDN, while inhibited that of NOx .NH4 + increased while NOx decreased during anoxic period. Fe(II) and TFe increased only in 3Fh, especially during anoxic conditions. Fh cappings increased O2 and H2 S concentrations across the water-sediment interfaces. TP and TN in the sediments decreased after capping, while TFe increased significantly. We concluded that 0.6 cm thickness of (496 g/m 2 ) Fh capping could sequestrate P, even experiencing redox conditions. Highlights: Reactive and intrinsic sediment capping materials are required and explored. Ferrihydrite (Fh) capping sequestrates filterable P effectively. Dissolution of the Fh caps subject to redox conditions is insignificant. Fh capping affects the distributions and balances of P, N, S and Fe. Thin Fh capping (0.6 cm thickness) could be used for in eutrophicated wetlands.